The Effect of Group Cognitive Behavioral Hypnotherapy on Increasing Self-esteem of Adolescents - Morteza Badeleh; Mahdi Fathi; Hamid Reza Aghamohammadian; Mohammad Taghi Badeleh (Golestan University of Medical Sciences, 2013)
Background and objective : Adolescence is a significant stage of social and psychosocial development. This particular period of crisis involves some problems, one of the most important ones is the loss of self-esteem . Hence, this study aimed at investigating the effect of group cognitive behavioral hypnotherapy on increasing adolescents' self-esteem .  Material and Methods: The research population ( n= 250) of the current study is the adolescents living in a boarding school of Taibad city, Iran, in 2012 academic year. Using convenience sampling, the subjects were selected and asked to fill out Copper Smite self-esteem Inventory, and considering the cut-off point of 23, 30 adolescences with the lowest self-esteem were randomly placed in two groups of control and experimental .The subjects of experimental group were taken part in 8 two- hour- long sessions of cognitive behavioral hypnotherapy while the ones of control group did not receive any training . At the end of this period, the subjects' self-esteem was measured again and compared with pre-test by Ancova test, using SPSS soft ware (version 19).  Results: Ancova test analysis indicates that the self-esteem score in group cognitive behavioral hypnotherapy compared with the control group is significantly increased (p<0.01).   Conclusion : Group cognitive behavioral hypnotherapy can lead to increased self-esteem in teenagers. Further researches accompanying by periods of follow-up are recommended.